A multiscale Cauchy–Born meshfree model for deformability of red blood cells parasitized by Plasmodium falciparum. (2017) - Zhang, L.W.; Ademiloye, A.S.; Liew, K.M.
Abstract: In normal physiological and healthy conditions, red blood cells (RBCs) deform readily as they pass through the microcapillaries and the spleen, however, upon invasion by the malaria parasite, the host RBC membrane begins to lose their deformability. In spite of the progress in understanding malaria pathogenesis, the primary mechanism responsible for the loss of deformability remains unclear. In this paper, we examine the effects of Plasmodium falciparum infection and maturation on the deformability of parasitized or infected red blood cells (iRBCs) by means of a three-dimensional (3D) multiscale red blood cell (RBC) framework. This multiscale framework is developed based on the Cauchy–Born rule and the meshfree IMLS-Ritz method. The atomistic scale strain energy density function of the RBC membrane was computed using a selected representative cell based on the membrane spectrin network. The results obtained from our numerical simulations affirm that the presence of malaria infection significantly increases the rigidity of RBC membrane. It was observed that in the trophozoite and schizont infection stages, biconcave cell geometry leads to better prediction than nearly spherical geometry in comparison with experimental studies. Furthermore, we confirm that increase in temperature also results to increased stiffening of the cell membrane. Lastly, the observed decrease in the deformability of iRBC membrane may be primarily due to the structural remodeling and changes in the microstructure of the membrane rather than the change in cell shape.